A case of adult onset disseminated juvenile xanthogranuloma - Havva Hilal Ayvaz; Gökçen Çelik; Müzeyyen Gönül; Arzu K?l?ç; Nimet Özcan; Aysel Çolak (Our Dermatology Online, 2016)
Juvenile xanthogranuloma (JX) is a rare, benign, non-Langerhans histiocytic proliferative disease that etiology is unknown. It is usually seen in children and infants. JX in adult is very rare. A 41-year-old female patient was admitted to our clinic with papules on her face, torso and extremities. A few lesions had occured 3 years ago on her face, they disseminated all over her body after having a traffic accident one year ago which for she had operations and she also concurrently was diagnosed asdiabetes mellitus (DM). Based on clinical and histopathological findings, the diagnosis of JX was made. There is no systemic involvement of JX detected. JX seen in adults are very rare and usually associated with hematological malignancy. The present case is a rare adult onset disseminated JX case without malignancy